Lyric enunciation in the context of lithurgical singing: the escape from signification - Alonso, Silvia (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
This paper deals with the particular way of enunciation that vocal liturgical music implies. The two most relevant features are its powerful pragmatic status and the high degree of performativeness of its utterances. In catholic liturgy we find an absolutely monological discourse under the appearence of a dialogical one. There is in our example -"Et Incarnatus est" from Mozart’s Mass in c minor- an scape from the importance of voice’s corporal aspect, which becomes just one more timbre among the wind section. The fact of the theological mistery implicit in the words being incomprehensive favours a true escape from signilïcation. We analize, then, the increasing presence of a strict non-verbal deixis. The contemplation of the theological mistery stops the way of the discourse, creates an hypertrophy of the musical setting of the words, and erases the corporal identity of the subject of the enunciation.